The Position and Polarization of the Distribution of Inheritance of Adopted Children in Merangin Regency Jambi Province - Rahmi Hidayati Al Idrusiah; Wahyu Sawaluddin; Muhammad Farhan HR; Amirulhakim bin Nadzri (Sekolah Tinggi Agama Islam Kuningan, 2026)
This study aims to examine the status of adopted children and the polarization of inheritance distribution in Merangin Regency, Jambi Province. The research method used is social legal research, which aims to understand legal phenomena within the social and cultural context in which the law operates. The results indicate that in Merangin Regency, adoption is not conducted in accordance with Islamic law. Adopted children are treated equally with biological children, and this also applies to inheritance distribution, resulting in them receiving more than one-third of the estate. This clearly contradicts Islamic law, which states that adopted children do not inherit; however, they are provided with the option of obtaining inheritance rights through a will or gift. The granting of mandatory will rights to adoptive children/parents by the Islamic Law Compilation of Islamic Law (KHI) represents a local feature of Islamic inheritance law in Indonesia. This legal breakthrough allows the regulation of wills in Islamic law to adapt to prevailing traditions. This study contributes to understanding how local customary practices in Merangin Regency diverge from classical Islamic inheritance principles, highlighting the tension between traditional adoption practices and the adaptive legal framework provided by KHI's mandatory will provisions.